The Power of Anti-Corruption Education in Shaping Social Attitudes: A Mediation Perspective - Widodo Widodo; Jossapat Hendra Prijanto; Rahayu Permana; Juniriang Zendrato; Triyani Ambar Sari (Jurnal Pemberdayaan Masyarakat, 2026)
Corruption cases continue to occur, potentially eroding social attitudes, including those of students. Therefore, this study aims to explore the influence of anti-corruption education on social attitudes through perceptions of corruption. The research uses a quantitative approach, survey methods, and a causal design. The population comprises 880 private junior high school students in Bekasi Regency, West Java, while the sample consists of 275 students. Sampling was conducted using a random proportional sampling method at each school. Data collection was conducted using a Likert-scale questionnaire, and analysis was conducted using the Structural Equation Modeling approach based on Partial Least Squares (SEM-PLS). The results show that anti-corruption education negatively affects perceptions of corruption and positively impacts students' social attitudes. Perceptions of corruption negatively affect students' social attitudes and mediate the influence of anti-corruption education on those attitudes. These findings yield new empirical evidence of the mediating role of perceptions of corruption in the causal relationship between anti-corruption education and students' social attitudes. This model makes theoretical contributions to psychology and educational management, particularly in shaping social attitudes through anti-corruption education. Furthermore, it can be used to optimize anti-corruption education as a strategy to prevent corruption and foster positive social attitudes among students.